1999
DOI: 10.1046/j.1469-7580.1999.19530387.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of neovascularisation of splenic autotransplants in mice

Abstract: The aim of this study was to examine the kinetics of neovascularisation of splenic autoimplants into the abdominal cavity after splenectomy in mice. Sixty-eight female Swiss mice were submitted to splenectomy. The spleen from each animal was sliced and the slices were implanted into the abdominal cavity. Groups of animals were killed after 1, 2, 3, 5, 7, 15, 21, 28, 42, 56, 70 and 84 d. Fluorescent polystyrene microspheres were injected via the orbital venous plexus before killing and the splenules we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Several animal model studies have assessed the effect of splenic autotransplantation on sepsis after splenectomy. Alves et al reported that after splenic autotransplantation in mice, there is neovascularization between the transplanted spleen and the main vessels on the third day after transplantation; the blood supply of the splenic fragments is eventually provided in a centripetal manner by the splenic, short gastric, mesenteric, and gastroepiploic arteries [ 24 ]. Patel et al showed that, in splenectomized rabbits, autotransplantation with small slices of spleen in the peritoneal cavity improves the clearance of pneumococci from the blood [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal model studies have assessed the effect of splenic autotransplantation on sepsis after splenectomy. Alves et al reported that after splenic autotransplantation in mice, there is neovascularization between the transplanted spleen and the main vessels on the third day after transplantation; the blood supply of the splenic fragments is eventually provided in a centripetal manner by the splenic, short gastric, mesenteric, and gastroepiploic arteries [ 24 ]. Patel et al showed that, in splenectomized rabbits, autotransplantation with small slices of spleen in the peritoneal cavity improves the clearance of pneumococci from the blood [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are corroborated by more recent studies of neovasculogenesis in murine transplants, with precise measurements enabled by injection of tracers (fluorescent polystyrene microspheres) and electron microscopy. Although the new vessels at the periphery of the grafts started to form on day 3 p/t, microcirculation within the marginal zone of white pulp remained rudimentary until week 10 p/t [ 48 ].…”
Section: Autotransplantations Of the Spleenmentioning
confidence: 99%
“…17 In mice, such grafts present centripetal revascularization after the third day following operation. 18 The most efficient function of these grafts however occurs after the 16th week. 19 Subtotal splenectomy with the preservation of the organ's inferior pole (STPI), has been described in dogs 7 and in rats.…”
Section: Introductionmentioning
confidence: 99%